Complete Ordering and Revealed Preference - Newman, Peter (Review of Economic Studies, 1960)
Complete Ordering and Revealed Preference Get access Peter Newman Peter Newman Jamaica Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 2, February 1960, Pages 65–77, https://doi.org/10.2307/2296128 Published: 01 February 1960